MODEL OF GREENHOUSE GAS EMISSION REDUCTION WASTE SECTOR IN DEPOK CITY - Agnesika Fitrisari; Rosadi Rosadi; Indarti Komala Dewi (Universitas Pakuan, 2021)
Waste is one of the largest sources of greenhouse gas emission (GHG) at the global, national, and Depok city levels. The purpose of this study was to analyze various alternative of reduction policy scenarios of the GHG waste sector used simulation model with dynamic system approach. The simulation applied from 2020 to 2050. There are four scenarios: BAU scenario, the current waste management; A scenario, based on the Jakstrada program; B scenario, the application of methane gas captured technology on Cipayung landfill, IPAL communal, and Septic tank; C scenario which is the application of Jakstrada program and methane gas captured technology on Cipayung landfill, IPAL communal, and septic tank. The amount of GHG waste sector in Depok 2020 is 414.966,80 Tons CO2/year. The largest amount of emission was originating from wastewater and waste accumulation in landfills, which is 232.053 Tons CO2/year and 173,864,8 Tons CO2/year. A scenario GHG is decreasing by 3,38%. B scenario is decreasing the GHG into 93,6% with 21,99% unmanaged waste and 7% burnt waste. C scenario was successfully decreasing 96,11% and 100% managed waste which is the most. For decreasing the GHG waste sector, it needs the waste management and the technology application are done simultaneously.